Parables Bernard of Clairvaux's mapping of spiritual topography - Birkedal Bruun, Mette 1967- (Leiden Boston Brill, 2007)
Preliminary Material /M. Birkedal Bruun -- Introduction /M. Birkedal Bruun -- Chapter One. Mappings /M. Birkedal Bruun -- Chapter Two. Topographies /M. Birkedal Bruun -- Chapter Three. Topographical Anthropology /M. Birkedal Bruun -- Chapter Four. Memory /M. Birkedal Bruun -- Chapter Five. Conclusion And Transition /M. Birkedal Bruun -- Chapter One. Introduction /M. Birkedal Bruun -- Chapter Two. Parabola I, De Filio Regis /M. Birkedal Bruun -- Chapter Three. Parabola II, De Conflictu Duorum Regum /M. Birkedal Bruun -- Chapter Four. Parabola III, De Filio Regis Sedente Super Equum /M. Birkedal Bruun -- Chapter Five. Parabola IV, De Ecclesia Quae Captiva Erat In Aegypto /M. Birkedal Bruun -- Chapter Six. Parabola V, De Tribus Filiabus Regis /M. Birkedal Bruun -- Chapter Seven. Parabola VI, De Aethiopissa Quam Filius Regis Duxit Uxorem /M. Birkedal Bruun -- Chapter Eight. Parabola VII, De Octo Beatitudinibus /M. Birkedal Bruun -- Chapter Nine. Parabola VIII, De Rege Et Servo Quem Dilexit /M. Birkedal Bruun -- Epilogue /M. Birkedal Bruun -- Bibliography /M. Birkedal Bruun -- General Index /M. Birkedal Bruun -- Index Of Bernard Texts /M. Birkedal Bruun.
This volume is a study of spatial structures in Bernard of Clairvaux’s Parables . It lays out a spiritual topography which is linked to the rumination of the Bible. The topography ranges across such locations as Paradise, Babylon, the bridegroom's chamber, and the Celestial Jerusalem, and man navigates it in the character of peregrinus and viator . The first part of the study addresses the spiritual topography and the hermeneutics of its mapping. The second and larger part examines each of Bernard's eight parables and the ways in which he reformulates issues central to monastic tradition – militia Christi , for example, God's image and likeness in man, contemptus mundi , the quest for beatitude – as voyages within spiritual landscapes
Includes bibliographical references and indexes
Keywords: Bernard -- of Clairvaux, Saint -- 1090 or 1091-1153; Bernard -- of Clairvaux, Saint -- 1090 or 91-1153; Bernard -- of Clairvaux, Saint -- 1090 or 91-1153; Spiritual Life -- Catholic Church; Spiritual Life -- Catholic Church; Spiritualiteit; Topografie; Hochschulschrift